Prenatal Diagnosis of Membranous Ventricular Septal Aneurysm Bulging from the Left Ventricle towards Right Atrium in a Fetus with a Tricuspid Atresia– Characteristics and Differential Diagnosis of Membranous Ventricular Septal Aneurysms - Walter, Adeline; Schneider, Martin BE; Faridi, Bettina; Geipel, Annegret; Gembruch, Ulrich (Cardiology and Cardiovascular Medicine, 2022)
Prenatal detection of membranous ventricular septal aneurysm requires clinical, morphological and functional evaluation, as the spectrum of a congenital ventricular out-pouching is vast and complex. Early pediatric cardiological presentation is needed, since clinical course during first year is variable.